2015
DOI: 10.14739/2310-1237.2015.1.42930
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characteristics of renal cell carcinoma with intravenous extension

Abstract: Ф ормирование опухолевых тромбов в просвете почечной и нижней полой вены (НПВ) представляет собой одну из особенностей почечно-клеточного рака. Данный феномен обнаруживают у 4-10% пациентов. Он до сих пор является предметом множества дискуссий как в клинической, так и в морфологической среде [1-3]. Фактически не изученными остаются иммуногистохимические характеристики этих опухолей и не сформулирована общая теория формирования внутривенозных неопластических тромбов. Считается, что способность почечно-клеточног… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It is known that with a decrease in tumor differentiation, the expression of CA9 is often reduced and even completely lost. Shchukin et al [16] showed a correlation between CA9 expression and tumor differentiation (Fuhrman nuclear grade); however, other researchers did not confirm this relationship [8]. According to some authors [10, 15], low expression of CA9 is associated with low cancerspecific survival, overall survival, and progression-free survival.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that with a decrease in tumor differentiation, the expression of CA9 is often reduced and even completely lost. Shchukin et al [16] showed a correlation between CA9 expression and tumor differentiation (Fuhrman nuclear grade); however, other researchers did not confirm this relationship [8]. According to some authors [10, 15], low expression of CA9 is associated with low cancerspecific survival, overall survival, and progression-free survival.…”
Section: Resultsmentioning
confidence: 99%